The Development of Experimental Electronic Student Activity Sheet (E-LKPD) using The Guided Inquiry Learning Model on Blood Circulation System Materials for Class XI SMA/MA - Suci Seftiani; Wan Syafii; Zulfarina Zulfarina (FKIP - Universitas Riau, 2022)
This e-LKPD research uses a guided inquiry learning model aimed at analyzing the effect of e-LKPD on improving cognitive learning outcomes of high school students on the material of the circulatory system. The study used the One Group Pretest-Posttest design model with the research subjects of class XI MIPA 3. At the beginning of the implementation students were given pretest questions, then students studied e-LKPD using a guided inquiry learning model and were given posttest questions. This e-LKPD was developed using the ADDIE model. This model consists of 5 stages of development, namely the Analyze, Design, Development. Implementation and Evaluation stages. The results of the research on the development of e-LKPD show that: The feasibility value by media experts is very valid 3.76 (94) and the feasibility value of material experts is very valid 3.42 (85.5) and the feasibility value of practitioners is very good 3.79 (94.75 ). Student and student responses are very practical, the practicality test by students is called trial 1 3.59 (89.75) and trial 2 by students 3.64 (90.78) This shows that e-LKPD using the kvisoft flipbook maker produced in this research This is considered feasible to be used in learning material about the circulatory system. Cognitive learning outcomes of students using e-LKPD development results increased from 30.4 to 90.35 with a high value increase (N-Gain: 0.85).